Study on tensile, flexural and impact strength of GLARE reinforced with sugarcane bagasse ash microparticles. (2021) - Dinesh Kumar, PK; Rajendran, Balaji; Subeetsha, Balavinayagar; Swetha, Nagaraj
Abstract: The study focuses on fabricating GLARE (Glass Laminate Aluminium Reinforced with Epoxy) composites with Sugarcane Bagasse Ash (SBA) that can be extensively used in the fuselage structure of aircraft, especially for its blast resistant properties. In this work, the effect of reinforcement of GLARE with varying agro-waste SBA (Sugarcane Bagasse Ash) microparticles such as 1%, 2%, and 3% by wt. in three cases was studied. The GLARE hybrid composites stocks were fabricated through the hand layup technique. Various static mechanical tests like tensile, flexural, and impact were made on tailored composites as per the ASTM standards to investigate the effects of SBA reinforcement. Results indicate the addition of bagasse-ash in GLARE composites with 3% by wt. provided greater effect and outperformed other hybrid GLARE composites.